2009
DOI: 10.1093/cercor/bhp155
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty during Anticipation Modulates Neural Responses to Aversion in Human Insula and Amygdala

Abstract: Uncertainty about potential negative future outcomes can cause stress and is a central feature of anxiety disorders. The stress and anxiety associated with uncertain situations may lead individuals to overestimate the frequency with which uncertain cues are followed by negative outcomes, an example of covariation bias. Using functional magnetic resonance imaging, we found that uncertainty-related expectations modulated neural responses to aversion. Insula and amygdala responses to aversive pictures were larger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
204
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 221 publications
(227 citation statements)
references
References 103 publications
(171 reference statements)
21
204
2
Order By: Relevance
“…Importantly, here perceptual evidence remains partial or incomplete at the time of overt decision (Response 1, see Methods). This situation could potentially generate a mild conflict, expressed by the urge to make a rapid decision while the actual accumulation of evidence is not complete yet (Hayden, Pearson, & Platt, 2009;Sarinopoulos et al, 2010;Scheffers & Coles, 2000). Thus, whereas the PCC/PHG complex may be involved in updating contextual information about the scene (based on the rapid extraction and accumulation of LSF information; see Bar, 2009) as SMA to a smaller degree.…”
Section: Brain Dynamics Of Upstream Perceptual Processes 28mentioning
confidence: 99%
“…Importantly, here perceptual evidence remains partial or incomplete at the time of overt decision (Response 1, see Methods). This situation could potentially generate a mild conflict, expressed by the urge to make a rapid decision while the actual accumulation of evidence is not complete yet (Hayden, Pearson, & Platt, 2009;Sarinopoulos et al, 2010;Scheffers & Coles, 2000). Thus, whereas the PCC/PHG complex may be involved in updating contextual information about the scene (based on the rapid extraction and accumulation of LSF information; see Bar, 2009) as SMA to a smaller degree.…”
Section: Brain Dynamics Of Upstream Perceptual Processes 28mentioning
confidence: 99%
“…Indeed, this has been demonstrated for various levels of emotional responding, including self-reported mood, valence, or pain intensity (Bar-Anan, Wilson, & Gilbert, 2009;Grupe & Nitschke, 2011;Ploghaus et al, 2001;Yoshida, Seymour, Koltzenburg, & Dolan, 2013) and autonomic reactivity (Grupe & Nitschke, 2011). Similarly, functional magnetic resonance imaging (fMRI) studies have revealed increased uncertainty-related activity in the amygdala and insula (Dunsmoor, Bandettini, & Knight, 2008;Ploghaus et al, 2001;Sarinopoulos et al, 2010;Yoshida et al, 2013), brain regions associated with the processing of emotional salience (Davis & Whalen, 2001;Straube & Miltner, 2011). Moreover, evidence from threat-of-shock paradigms has suggested that uncertainty elicits defensive motivation, which is associated with increased physiological reactivity and hypervigilance.…”
mentioning
confidence: 94%
“…Conditions of unpredictable negative events are associated with sustained anxiety and apprehension (Davis, Walker, Miles, & Grillon, 2010;Grillon, 2008;Grupe & Nitschke, 2013) and give rise to the search for strategies to reduce uncertainty-for example, by correctly assessing contingencies (Alloy & Tabachnik, 1984). However, the ability to assess contingencies is impaired, as is indicated by research demonstrating illusory correlations between cues ambiguously signaling potential threat and subsequent aversive events (Grupe & Nitschke, 2011;Sarinopoulos et al, 2010;Wiemer, MĂŒhlberger, & Pauli, 2014). Sarinopoulos and colleagues utilized a passive picture-viewing paradigm in which a cue indicated whether a subsequent picture would be neutral or aversive (certain conditions), or either of the two (uncertain condition).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The prestimulus state of brain areas involved in perceptual decisions may therefore also reflect information about the significance of an impending stimulus. For instance, Sarinopoulos et al (2010) recently showed that uncertainty-related expectations lead to an overestimation of the frequency by which uncertain cues are followed by negative outcome and amplified neural responses to aversion. Importantly, it is the subjective interpretation of available information that influences perceptions and actions, regardless of whether it is factually true or not.…”
Section: Introductionmentioning
confidence: 99%